THE EFFECT OF WORK ETHIC AND DISCIPLINE ON EMPLOYEE’S PRODUCTIVITY AT VILLAGE BUSINESS OFFICE (BUMDES) IN LUTUR VILLAGE SOUTH NORTH ARU DISTRICT - Kriekhoff, Shella (jfpublisher, 2022)
This research was conducted at Village Owned Enterprises Office (BUMDES) in Lutur Village, North South Aru District. This study uses work ethic and discipline as independent variables, and work productivity as the dependent variable. The purposes of this study were to determine the effect of work ethic and discipline on employees’ work productivity at the Village Owned Enterprise (BUMDES) Lutur Village, North South Aru District, and to determine the dominant variables between work ethic and discipline on employees’ work productivity at Village Owned Enterprise (BUMDES) Lutur Village, North South Aru District. The sample used is Amaris Hotel Ambon employees with a total sample of 37 respondents. The analysis used includes validity test, reliability test, model test, and multiple linear regression analysis and research hypotheses. Based on the results of the research, it can be seen that work ethic and discipline in this study proved to have a significant influence on work employees’ productivity at Village Owned Enterprise (BUMDES) Lutur Village, North South Aru District. Also, work ethic is the dominant variable that affects the employees’ work productivity at the Village Owned Enterprise (BUMDES) Lutur Village, North South Aru District. In this study, it was found that the variation in employee performance explained by work ethic and discipline is 74.8% while 25.2% was explained by other not-analyzed variables, including work stress, work environment, etc.